Identifying Royal College-accredited simulation centre research priorities across Canada - Harley, Jason M; Lau, Clarissa Hin-Hei; Bilgic, Elif; Muller Moran, Ricky; Fried, Gerald M; Bhanji, Farhan (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
To advance the field of health sciences simulation, research must be of high quality and would benefit from multi-institutional collaboration where centres can leverage and share expertise as well as work together to overcome limits to the generalizability of research findings from single-institution studies. A needs assessment in emergency medicine simulation has illustrated the importance of identifying research priorities in Canada. The main purpose of this study was to identify simulation research priority directions for Canadian simulation centres. The current survey study drew on 16 research priorities developed through a two-round internal Delphi study at McGill University that 15 of 17 simulation centre advisory board members participated in. The final 16 research priorities were then rated by a total of 18 of 24 simulation centre directors and/or delegates contacted from 15 of 19 Royal College of Physicians and Surgeons of Canada-accredited simulation centres in Canada. Results revealed 9 common research priorities that reached 70% or higher agreement for all respondents. We anticipate that our findings can contribute to building a shared vision of priorities, community, and collaboration to enhance health care simulation research quality amongst Canadian simulation centres.